LEGAL PROTECTION OF LITERARY ARTISTS' COPYRIGHTS IN BANDAR LAMPUNG - Agit Yogi Subandi; M. Wendy Trijaya; Made Widhiyana; Sepriyadi Adhan S; Sona Asnawi (Law Faculty of Universitas Bandar Lampung, 2025)
Literary works are a form of creative expression protected by Law Number 28 of 2014 concerning Copyright. Literary work copyright gives the author exclusive authority to manage and profit from his work. Bandar Lampung City artists have received much national and international recognition for their works, both in the form of poetry, short stories, novels and theater plays. However, the risk of copyright infringement increases with the influence and popularity of Bandar Lampung literary works. There are still many works by artists in Lampung, especially literature, that are modified and used by other people without the owner's permission. Therefore, this article will review the extent of knowledge of artists in Bandar Lampung. It is hoped that this outreach can help increase awareness of the Copyright Law in Lampung Province and the importance of protecting the works of literary artists.